Motivational Factors Affecting the Choice of Meal Replacement Supplements among Generation Z Consumers in Bangkok - Wangkorkiat, Nattapat; Singlumpong, Ongart (Siam Communication Review, 2025)
This research aimed to study the motivation communication strategies that affect the decision to consume meal replacement supplements among Generation Z consumers in Bangkok. The quantitative research method was used to collect data via an online questionnaire with a sample group of Generation Z in Bangkok. The results of the research found that the demand for meal replacement supplements of the Generation Z sample group in terms of gender did not affect the decision-making process. The researcher inferred that the reason for the lack of difference may be because there are currently more genders than males and females, namely the LGBTQ+ group. This group is a variable that causes the attitudes of men to change more and is the point that led to the results that different genders will affect the decision to consume meal replacement supplements equally. In addition, the aspect of saving is also a part of the decision-making process. The research results pointed to the fact that saving is the main reason for deciding to purchase meal replacement supplements among the Generation Z sample group in Bangkok. The results of this research can be used to adjust the marketing strategies of food supplement entrepreneurs because they can identify the limitations and needs of Generation Z consumers from the research results. It can also be a part in helping to improve and create more understanding and attitudes between consumers and food supplement entrepreneurs. Keywords: communication strategies, motivations that affect consumption choices, choosing to consume food supplements as a replacement for main meals.